Integrating Digital Technology into Disaster Education and Its Impact on Elementary School Students’ Literacy and Resilience - Haryati, Sri; Atmojo, Setyo Eko; Anggriani, Mitha Dwi; Skotnicka, Michalina (FKIP Universitas Lampung, 2025)
Integrating Digital Technology into Disaster Education and Its Impact on Elementary School Students’ Literacy and Resilience. Indonesia is one of the countries with the highest risks of natural disasters in the world; hence, disaster education in elementary schools is an urgent need. Objective: This study aims to analyze the effectiveness of digital technology-based disaster education in improving the disaster literacy and resilience of elementary school students in areas prone to volcanic eruptions. Methods: This study used a quasi-experimental design with a nonequivalent control group design. The research sample consisted of elementary school students living in disaster-prone areas. The instruments used included a disaster literacy test, a resilience questionnaire, and interviews with teachers and students to strengthen the quantitative results. Data analysis was conducted using a paired sample t-test to examine differences within groups and an independent sample t-test to compare differences between groups. Findings: The results showed a significant increase in the experimental group compared to the control group. The disaster literacy score in the experimental group increased from 47.67 to 82.17, and the resilience score from 58.60 to 80.30. Meanwhile, the control group only experienced a lower increase. The paired sample t-test results showed a significant difference (p < 0.05). The control group did not experience a significant increase in the number of participants. The independent sample t-test also confirmed a significant difference between the two groups in their posttest scores, with an average difference of 15.84 points for disaster literacy and 14.30 points for resilience. Qualitative data supported these results, with teachers rating interactive digital media as facilitating the understanding of evacuation and simulations, while students found the learning more engaging and easier to practice. Conclusion: This study demonstrates that digital technology-based disaster learning is more effective than conventional methods in enhancing the literacy and resilience of elementary school students. The implication is the importance of integrating digital technology into the disaster education curriculum, so that students not only understand the theory but are also able to adapt, be resilient, and take appropriate action when facing disasters in their environment. Keywords: disaster education, technology, digital, disaster literacy, disaster resilience.